Effect of Impact Cavity Shape Induced by Supersonic Oxygen Jet on the Dynamic Characteristics of Molten Bath in Converter. Issue 9 (26th July 2021) - Sun, Jiankun; Zhang, Jiangshan; Lin, Wenhui; Cao, Lingling; Feng, Xiaoming; Liu, Qing
Abstract : The cavity shape formed by the impinging of the supersonic oxygen jet on liquid metal surface is of importance to the converter steelmaking process. This work adopts the volume of fluid (VOF) model to numerically study the behavior of four‐nozzle supersonic jet impinging on molten steel bath in a 100 ton converter. First, the model is validated by comparing the jet velocity with that obtained from the literature. After validation, the dynamic interaction between supersonic jet and molten bath is studied. Moreover, the effects of lance height and operating pressure on the impact cavity depth and diameter are investigated. Compared with operating pressure, lance height shows a larger influence on altering the cavity dimensions. To quantitatively describe the profile of the scattered cavities, a dimensionless number called the modified cavity shape index ( I cm ) is put forward, which has a significant influence on the velocity distribution and specific kinetic energy of molten bath. The modified cavity shape index is found to be a function of the specific kinetic energy. With the modified cavity shape index ranging from 1.47 to 1.72, the dynamic flow of the molten bath becomes beneficial to the stirring and mixing of the molten bath. Abstract : The scattered cavities are produced by the four‐hole supersonic jet impinging on the molten bath. The lance height can change the cavity shape notably more than the operating pressure. When the modified cavity shape index is controlled at 1.47–1.72, the molten bath dynamic characteristics are more conducive to the stirring and mixing of the molten bath.